2020
DOI: 10.1021/acsomega.0c00170
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Suppression of a Fe-Supported Catalyst and its Utilization for Low-Temperature Ammonia Synthesis in an Electric Field

Abstract: Fe-supported heterogeneous catalysts are used for various reactions, including ammonia synthesis, Fischer–Tropsch synthesis, and exhaust gas cleaning. For the practical use of Fe-supported catalysts, suppression of Fe particle agglomeration is the most important issue to be resolved. As described herein, we found that Al doping in an oxide support suppresses agglomeration of the supported Fe particle. Experimental and computational studies revealed two tradeoff Al doping effects: the Fe particle size decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…5 wt% of Fe was loaded over synthesized CeO 2 -based materials using a liquid-phase reduction method as reported elsewhere. 45 First, Fe(NO 3 ) 3 Á9H 2 O (Kanto Chemical Co. Inc.) was poured into distilled water. The support was dispersed in the obtained Fe aqueous solution by stirring for 1 h. Subsequently, the solution was heated at 393 K for 1 h under Ar flow.…”
Section: Preparation Of Fe-supported Ceo 2 -Based Materialsmentioning
confidence: 99%
“…5 wt% of Fe was loaded over synthesized CeO 2 -based materials using a liquid-phase reduction method as reported elsewhere. 45 First, Fe(NO 3 ) 3 Á9H 2 O (Kanto Chemical Co. Inc.) was poured into distilled water. The support was dispersed in the obtained Fe aqueous solution by stirring for 1 h. Subsequently, the solution was heated at 393 K for 1 h under Ar flow.…”
Section: Preparation Of Fe-supported Ceo 2 -Based Materialsmentioning
confidence: 99%
“…For this purpose, fluorite binary oxides such as CeO 2 34 and perovskites such as SrZrO 3 41, 42 are good candidates. The choice of catalyst support should be considered based on its physical properties 45 : conductors such as Fe 2 O 3 can sustain an electric current but do not promote catalytic activity, whereas insulators such as Al 2 O 3 cannot sustain sufficient surface protonic current, and the electric field results only in discharge. Only semiconducting type supports such as CeO 2 and SrZrO 3 appear to satisfy the required physical properties: Surface protonic conductivity is a key factor, but also the presence of redox-active cations and possibly electronic transport seem important.…”
Section: The Catalystsmentioning
confidence: 99%
“…Hydrogen migration plays an important role in various catalyses such as hydrogenation-dehydrogenation of hydrocarbon, 1-5 CO 2 reduction [6][7][8][9] and NH 3 synthesis. [10][11][12][13][14][15][16][17] However, the utilisation of hydrogen migration is not limited to catalysis. It is also fundamentally important for catalyst preparation, 18,19 hydrogen storage, 20,21 fuel cells and sensors.…”
Section: Overviewmentioning
confidence: 99%
“…[39][40][41] This active migration is called surface protonics. It has been revealed that surface protonics plays a key role in activating the cleavage of strong bonds, as in the NRN bond in N 2 , [13][14][15][16][17]42,43 and the C-H bond in hydrocarbons, as in CH 4 [42][43][44][45][46] and methylcyclohexane (MCH). 4,5 Those activations make it possible to catalyze hydrogen production and formation of the hydrogen carrier, even at low temperatures (o500 K).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation